2014
DOI: 10.1186/1478-811x-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Downstream signaling and genome-wide regulatory effects of PTK7 pseudokinase and its proteolytic fragments in cancer cells

Abstract: BackgroundThe full-length membrane protein tyrosine kinase 7 (PTK7) pseudokinase, an important component of the planar cell polarity and the Wnt canonical and non-canonical pathways, is a subject of step-wise proteolysis in cells and tissues. The proteolysis of PTK7 involves membrane type-matrix metalloproteinase (MT1-MMP), members of the Disintegrin Domain and Metalloproteinase (ADAM) family, and γ-secretase. This multi-step proteolysis results in the generation of the digest fragments of PTK7. These fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Therefore, differences in the composition of the PTK7 co-receptor complex may explain these contradictory findings in different tissue settings. This is also supported by reports concerning PTK7 downstream signaling, where various signaling outcomes like activation of c-jun, AKT, Ras/ERK, CREB/ATF1, SRC and inhibition of JNK signaling were observed [ 39 , 40 , 41 , 42 ]. The fact that PTK7 interacts with other receptors like Plexin and VEGF receptors further supports this hypothesis and suggests that PTK7 is a versatile co-receptor [ 43 ].…”
Section: Introductionsupporting
confidence: 82%
“…Therefore, differences in the composition of the PTK7 co-receptor complex may explain these contradictory findings in different tissue settings. This is also supported by reports concerning PTK7 downstream signaling, where various signaling outcomes like activation of c-jun, AKT, Ras/ERK, CREB/ATF1, SRC and inhibition of JNK signaling were observed [ 39 , 40 , 41 , 42 ]. The fact that PTK7 interacts with other receptors like Plexin and VEGF receptors further supports this hypothesis and suggests that PTK7 is a versatile co-receptor [ 43 ].…”
Section: Introductionsupporting
confidence: 82%
“…Ptk7 has additionally been linked to breast cancer [ 47 , 48 , 49 ] and leukemia [ 50 , 51 , 52 , 53 ]. Recently, Ptk7 was implicated in cancer cell motility and metastasis in fibrosarcoma HT1080 cells, identified as a potential diagnostic biomarker for a variety of cancer types [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and proposed as a tumor suppressor gene by inhibiting ERK and AKT phosphorylation in lung cancer [ 39 ].…”
Section: The Transmembrane Receptor Ptk7mentioning
confidence: 99%
“…In addition, much like the invertebrate function of Otk, in vertebrate development, Ptk7 interacts with plexin A1 regulating neural crest migration [ 70 , 71 , 72 ]. Ptk7 is cleaved by a membrane type matrix metalloprotease (MT1-MMP) affecting its function in both zebrafish and human development, and cancer cell metastasis [ 61 , 73 , 74 , 75 , 76 ]. Taken together, these findings suggest that Ptk7 is a highly regulated, polarity-determining molecule in a variety of cellular behaviors both during development and in cancers.…”
Section: The Transmembrane Receptor Ptk7mentioning
confidence: 99%
“…Recently, it was reported that PTK7, alone as well as in combination with MT1-MMP, ADAMs, and g-secretase, play important roles in cancer cell migration [38]. Additionally, both the PTK7 silencing and overexpression fully blocked the ability of fibrosarcoma HT1080 cells to metastasize to the lungs in nude mice and diminished productive cell invasion in a chick embryo model [39].…”
Section: Discussionmentioning
confidence: 98%